Components of Collective Leadership of School Administrators - Chaibuppha, Jirat; Phengsawat, Waro; Chalarkbang, Wannika (Journal of Graduate MCU KhonKaen Campus, 2024)
The purpose of this research is Components of the Collective Leadership of School Administrators. The study is divided into two steps, The first step is the Dialogue synthesis of among administrators of educational institutions. Which study from 10 theoretical ideas and research papers. Step 2 to evaluate the Dialogue used by Appropriate of Five experts. The document synthesis form and 5-rating scale which indicated content validity index ranged 0.90 questionnaire were the research instruments. Frequency, percentage, mean, and standard deviation were employed in data analysis. The study revealed that there were four School Administrators Collective Leadership elements: 1) Teamwork, 2) Personnel Development, 3) Participation, and 4) Network and partnership management. Moreover, all of these Elements were the highest appropriate level